Distributed beamforming and wireless broadcast advantage for routing in wireless mesh networks - Ali, Towfik Jemal; Kern, Daniel; Kuehn, Volker (Proceedings (African Electrical Technology Conference), 2015)
Wireless broadcast advantage (WBA) and wireless cooperative advantage (WCA) are exploited in this paper for finding a cooperative route in a wireless mesh network with minimum energy consumption considering practical coding and modulation schemes. In doing so we have assumed a multihop wireless mesh network consisting of nodes capable of adjusting their transmit power. An optimization problem to allocate minimum sum power for a given route subject to a desired end-to-end throughput and outage probability constraints is formulated. WBA and WCA are taken into account separately and together during the resource allocation. Afterwards, optimal and suboptimal route selection is done using a classical Dijkstra's algorithm. Turbo codes with iterative decoding algorithms are implemented with various QAM modulation schemes.